A model for the performance monitoring and evaluation of organizations to migrate to the cloud based on system approach / Jalal Sarabadani and Ayoub Mohammadian. - Sarabadani, Jalal; Mohammadian, Ayoub (Universiti Teknologi Mara Selangor, 2015)
In recent years, the concept of cloud computation has been an issue of great importance both for researchers and practitioners. This paper aims to assess the performance of cloud computing from the business perspective, when the organizations want to migrate to the cloud environment.In this paper, the criteria related to performance evaluation are extracted by a system approach, based on content analysis and Shannon entropy research methods. The results show that financial, technological, operational and strategic outcomes are important parameters for strategists to plan for migrating to the cloud environment.